Improvement of haemodynamic stent strut configuration for patent ductus arteriosus through computational modelling - Taib, Ishkrizat (2016)
CurTently, the treatment of Patent Ductus Arteriosus (POA) by the implantation of coronary stent has resulted in severe hemodynamic complications. There is thus a need to customize and improve current stent geometry specific to POA to overcome this problem. Computational Fluid Dynamics (CFO) approaches, verified by an experimental technique are used to analyze current stent strut configurations. Statistical analysis is used to rank the parameter performance and to obtain the best stent configuration. The most favorable configuration is then used to design new stent strut configuration specific for PDA. In the analysis of the new stent design, CFO results show low possibility of re-stenosis process due to thrombosis formation, inflammation, and nee-intimal hyperplasia. Furthermore, comprehensive CFO analysis by solving fluid-structure interaction (FSI) cases has produced an optimum stent strut configuration that is structurally sound. The strength of stent strut configuration due to hemodynamic effect is analyzed through the Von Misses stress distribution. The results show that the new improved design of stent strut configuration has excellent hemodynamic performance. Finally, the new stent design is predicted to be able to overcome hemodynamic complications and stent structural failure when applied specifically to PDA